The hot book & the cold book - Goldsmith, Mike (1962-); Smith, Miranda Illustrator (London : Scholastic, 2015)
This stunning series is packed with cross-curricular information, case studies and dazzling photography. Exploding volcanoes, sizzling start and fire-breathing dragons... enough burning hot facts to make you sweat! Ship-sinking icebergs, frozen planets, abominable snowmen... enough facts and fun about the cold to give you goosebumps!
Keywords: Cold; Heat